Energy efficiency of heterogeneous cellular networks: A review - Abdulkafi A.A.; Kiong T.S.; Koh J.; Chieng D.; Ting A. (2023)
The concept of heterogeneous networks had been proposed as an alternative approach to provide higher capacity and coverage for cellular networks. Along with that the aspect of "Energy Efficiency" had already received much attention lately due to ecological as well as economic reasom particularly for network operators. Ths study presented a systematic review on the topic of energy efficiency in heterogeneous cellular networks. The review was dvided into three parts; first the typical metrics parameters used to measure energy efficiency and tradeoff relationships with respect to network performance were dscussed. Next the existing issues, approaches and challenges to provide energy efficiency in general cellular networks were addressed. Finally we looked into the current effoa on energy awareness in macro, micro, pico and femtocells. By means of discussions, we highlighted dfferent heterogeneous network scenarios in which network planning and optimization techmques were (or not were) advantageous to provide essential understanding for successful deployment of green heterogeneous cellular networks. 2012 Asian Network for Scientific Information.